Advancements in the treatment of non-alcoholic fatty liver disease (NAFLD) - Rong, Li; Zou, Junyan; Ran, Wei; Qi, Xiaohong; Chen, Yaokai; Cui, Hongjuan; Guo, Jinjun (Frontiers in Endocrinology, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a series of diseases, involving excessive lipid deposition in the liver and is often accompanied by obesity, diabetes, dyslipidemia, abnormal blood pressure, and other metabolic disorders. In order to more accurately reflect its pathogenesis, an international consensus renamed NAFLD in 2020 as metabolic (dysfunction) associated with fatty liver disease (MAFLD). The changes in diet and lifestyle are recognized the non-drug treatment strategies; however, due to the complex pathogenesis of NAFLD, the current drug therapies are mainly focused on its pathogenic factors, key links of pathogenesis, and related metabolic disorders as targets. There is still a lack of specific drugs. In clinical studies, the common NAFLD treatments include the regulation of glucose and lipid metabolism to protect the liver and anti-inflammation. The NAFLD treatments based on the enterohepatic axis, targeting gut microbiota, are gradually emerging, and various new metabolism-regulating drugs are also under clinical development. Therefore, this review article has comprehensively discussed the research advancements in NAFLD treatment in recent years.